Nurturing Inherent Nobility: Insights on Human Dignity from a Bahá’í Perspective - Temily Tianmay Tavangar; David Alexander Palmer (Religions, 2023)
The Bahá’í Faith is an important case for a discussion on dignity, religion and human rights. Beyond the notions of dignity enshrined in its basic teachings, a core concern of the Bahá’í community is how to build dignity into the pattern of social relations of an emerging global civilization. The oneness of humanity is the core principle around which all Bahá’í teachings revolve, and within this principle is enshrined not only the inherent, God-given nobility and dignity of every individual but also the responsibility of creating new patterns of social relations, forms of community, processes of education, and structures of institutional authority that consciously strive to create a global polity that protects and affirms the dignity of all humans, in all of their diversity. In this paper, we examine the foundations of human dignity in the Bahá’í Faith in four parts. First, we explore the use of the term “dignity” in Bahá’í sacred texts and its relationship to the concepts of “nobility" and “rights”. Second, we examine how Bahá’ís seek to put into practice their conception of dignity through a democratic system of global governance, grounded in processes of consultative deliberation, referred to as the Bahá’í Administrative Order. Third, we highlight how the Bahá’í community is seeking to cultivate conditions of dignity in its current educational endeavours, which seeks to contribute to the betterment of local communities throughout the world. Fourth, we explore the ongoing and centuries-long persecution of the Bahá’ís in Iran to understand the implications of dignity in responding to oppression.